Penguatan Kapasitas Guru SD Negeri 38 Lubuklinggau Dalam Penyusunan Asesmen Berbasis Live Worksheet - Friansah, Drajat Friansah; Yanto, Yufitri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to increase the role and participation of PGRI Silampari University in providing solutions and targeting problems faced by the community, in this case teachers at SD Negeri 38 Lubuklinggau. The long-term goal is to increase inclusivity in learning in elementary schools. The method used is Peer Assisted Learning Strategies which consists of 6 stages: 1) problem identification, 2) designing needs analysis, 3) workshop and mentoring, 4) implementation, 5) monitoring and observation of activities, and 6) reports and follow-up. The results obtained showed that there was an increase in teachers' builiding capacity in the skill of compiling statistical literacy assessment instruments based on live worksheets, in addition to that there was an increase in the average knowledge of assessment from 7.5 to 8.4. The teacher gave a positive response during the workshop.